Changes in diet quality during a 12 month weight loss randomised controlled trial - Wibisono, Cinthya (BMC Nutr, 2017)
BACKGROUND: Reductions in energy intake are seen in weight loss trials, but whether this occurs with improvements to diet quality (DQ) is less established. The aim of this study was to evaluate changes in diet quality in a sample of volunteers in a weight loss trial. METHODS: This was a secondary analysis of dietary data from a lifestyle intervention trial (the HealthTrack study) which advised on dietary guidelines. The trial ran for 12 months with three treatment groups: control (general advice C), intervention (individualised advice, I), and intervention plus a supplement of walnuts (IW). Both the published a priori diet quality score (APDQS, maximum score 164) and a study specific Diet Quality Tracker (DQT, maximum score 44) indicated compliance to dietary advice. DQ scores calculated at 0, 3months and 12months were evaluated using two-way RMANOVA, one-way ANOVA and one-way RMANOVA. Changes in intakes of food groups and nutrients were analysed using Kruskal-Wallis and Friedman’s tests. RESULTS: There were no differences between groups at baseline, but at 3months IW recorded higher DQ scores (APDQS:96 ± 10; DQT:22 ± 5, P < 1 × 10(−3) for both) compared to I (APDQS:91 ± 13, P < 1 × 10(−3); DQT:21 ± 4, P < 1 × 10(−2)) and C (APDQS:87 ± 12, P < 5 × 10(−2); DQT:19 ± 4, P > 5 × 10(−2)), and a higher consumption of nuts at 3 months (P < 1 × 10(−3)), and 12months (P < 1 × 10(−2)). All groups reported decreased intakes of discretionary foods/beverages assessed by the DQT (P < 1 × 10(−3) for IW and I; P < 1 × 10(−2) for C). The APDQS showed this as reduced intakes of grain based desserts (P < 1 × 10(−3) at 3 and 12months), and salty snacks at 12months (P < 1 × 10(−3) for IW and I; P < 5 × 10(−2) for C). Intakes of monounsaturated and saturated fatty acids were lowest, and polyunsaturated fatty acids highest for IW (P < 1 × 10(−3)), resulting in a higher dietary polyunsaturated:saturated fat ratio (P < 1 × 10(−3)). CONCLUSIONS: Lifestyle intervention addressing dietary guidelines can lead to significant reductions in consumption of discretionary foods and saturated fat, but individualised advice may have a greater impact on improving overall DQ regardless of DQI used. Providing a healthy food supplement may help assure higher DQ and where the food is walnuts, produce commensurate differences in dietary fatty acid profiles. TRIAL REGISTRATION: ANZCTRN 12614000581662. Date of registration: 30th May 2014. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40795-017-0157-z) contains supplementary material, which is available to authorized users.